Pelatihan Pengelolaan Lingkungan Cerdas melalui Budidaya Maggot Berbasis Komunitas di Desa Dewasari, Kabupaten Ciamis - Erlan Suwarlan; Irfan Nursetiawan; Ii Sujai; Regi Refian Garis; Aditiyawarman; Afishah Alias (Fakultas Teknik Universitas Cenderawasih, 2026)
The primary challenge faced by the community in Dewasari Village, Ciamis Regency, is the ineffective management of household organic waste, along with limited knowledge and skills in converting organic waste into value-added products. This community service program aimed to strengthen community capacity in developing smart environmental management through community-based Black Soldier Fly (BSF) maggot cultivation. The program was implemented through educational sessions, practical training on BSF maggot cultivation, community mentoring, and learning evaluation using a participatory approach involving the village government, community groups, and local youth. The results showed significant improvements in participants' knowledge and practical skills in managing organic waste, cultivating BSF maggots independently, and utilizing the harvested maggots as alternative livestock feed and an additional source of household income. The program also increased community awareness of the importance of sustainable and environmentally friendly waste management. Therefore, community-based BSF maggot cultivation can serve as an innovative solution for promoting smart, productive, and sustainable environmental management while strengthening community economic empowerment and improving household livelihoods in Dewasari Village.